The Concept of Information Modeling in Interactive Intelligence Systems - Sinitsyn, S. (Springer, 2020)
A personâs daily life is a sequence of decisions made on the basis of a certain amount of information that he has from various sources, including his own experience. To make the right decision need to get the amount of information not below a given level. Information is distinguished not only by its quantity, but also by the degree of heterogeneity, which does not allow its simple summation. Decisions made on the basis of available information are often wrong, and their consequences are negative. Different, including heuristic models are needed, which could calculate the consequences of the decisions taken and predict the result. Decisions are made within the confidential ranges, the values of which reflect the volume and quality of the processed information. A formulation of an optimization task that minimizes the likelihood of making the wrong decision is proposed. Â© 2020, Springer Nature Switzerland AG.